Аналіз парків кар’єрних самоскидів підприємств центральної частини України - Монастирський, Ю. А.; Гальченко, А. В.; Вівчарик, А. С. (НТУ "ХПІ", 2014)
На основі статистичних даних встановлені розподіли кар’єрних самоскидів в центральній частині України по вантажопідйомності, рокам експлуатації і моделям. Встановлено, що парк кар’єрних самоскидів вантажопідйомністю 30-45 т представлений в основному машинами які вироблені більше 20 років назад. Найбільш стабільний по віку та моделям парк кар’єрних самоскидів вантажопідйомністю 120-130 т.

The distributionsof open-pit dump-trucks in central part of Ukraine on a carrying capacity, years of exploitation and models, which based of statistical data, are set. It is set that park of open-pit dump-trucks by the carrying capacity of 30-45 t presented mainly by the machines produced more than 20 years back. Most stable on age and to the models park of open-pit dump-trucks by a carrying capacity 120-130 t.
Analysis park open-pit dump-trucks enterprise of the central part of Ukraine
Keywords: кар’єрний самоскид; фірмовий сервіс; парк машин; моделі самоскидів; open-pit dump-trucks; brandname service; park of machines; age of open-pit dump-trucks; model of open-pit dump-trucks; BelAZ